Protective effects of chokeberry (Aronia melanocarpa (Michx.) Elliott) fruit extracts against cisplatin-induced nephrotoxicity in rats - Milutinović, Milica; Ćujić Nikolić, Nada; Šavikin, Katarina; Cvetković, Tatjana; Janković-Veličković, Ljubinka; Djordjević, Ivana; Randjelović, Milica; Miladinović, Bojana; Kitić, Dušanka (Archives of Pharmacy, 2022)
Chokeberry (Aronia melanocarpa (Michx.) Elliott) is a rich source of pharmacologically active compounds. Nephrotoxicity is the most common side effect of cisplatin therapy. The aim of the study was to investigate the protective effects of chokeberry fruit extracts in rats with cisplatin-induced acute kidney injury. The dried plant material (whole chokeberry fruit and waste, the rest of the fruit left behind after squeezing the juice) was extracted by maceration using 50% ethanol, and then the extracts were lyophilized in order to better preserve the polyphenols. The content of total polyphenols, anthocyanins, proanthocyanidins and flavonoids in the extracts was determined by the spectrophotometric procedures , while the high-pressure liquid chromatography was used to quantify individual anthocyanins and flavonoids. The protective effects of chokeberry extracts were evaluated by the values ​​of biochemical, antioxidant, and anti-inflammatory markers of acute kidney injury in plasma and tissue, as well as histopathological analysis in different rat groups. By comparing the effects of the tested preparations, it was found that the extracts could reduce kidney damage in cisplatin-treated rats. Histopathological analysis showed the changes localized in the renal tubules, so the protective effects of chokeberry preparations are also observed there. Levels of antioxidant and anti-inflammatory markers in plasma and tissue also indicate a significant protective activity of extracts. The waste extract had more pronounced activity compared to the whole fruit extract, probably due to the higher concentration of polyphenolic compounds, primarily anthocyanins. Chokeberry extracts can alleviate cisplatin-induced nephrotoxicity, due to their antioxidant and anti-inflammatory effects.